Transformation of 2,4, 6-Trinitrotoluene (TNT) by Immobilized and Resting Cells of Arthrobacter SP. - A. M. Tope; K. Jamil; T. R. Baggi (Journal of Hazardous Substance Research, 1999)
Arthrobacter sp. transformed 2,4,6-trinitrotoluene (TNT) into two isomeric monoaminodinitrotoluenes viz, 4-amino-2,6-dinitrotoluene (4-ADNT), 2-amino- 4,6 –dinitrotoluene (2-ADNT) and also 2,4- diamino-6- nitrotoluene (2,4-DANT) under aerobic resting cell conditions. Experiments were carried out at 30° C (±1°C) in phosphate buffer with 60 mg per liter TNT at a pH of 7.2 (±0.2). Complete transformation of TNT occurred within 36 hours, yielding a mixture of monoaminodinitrotoluenes and diaminonitrotoluene. The major component was found to be 4-ADNT. Under the same experimental conditions, transformations were studied using barium alginate immobilized cells of Arthrobacter sp. Appropriate controls were run simultaneously. In both the cases, reactions were monitored every six hours by thin-layer chromatography (TLC) and gas chromatography (GC). The products were identified by gas chromatography coupled with mass spectrometry (GC-MS). Immobilization of Arthrobacter sp. in barium alginate resulted in more efficient TNT transformations, which were complete in 24 hours. The immobilized cells could be utilized at least for eight cycles and a decrease in rate of transformation was observed with each cycle.
Keywords: monoaminodinitrotoluenes; dinitrotoluene; Arthrobacter sp.; gas chromatography; mass spectrometry